2016
DOI: 10.1042/bcj20160340
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a high-affinity sialic acid-specific CBM40 from Clostridium perfringens and engineering of a divalent form

Abstract: CBMs (carbohydrate-binding modules) are a class of polypeptides usually associated with carbohydrate-active enzymatic sites. We have characterized a new member of the CBM40 family, coded from a section of the gene NanI from Clostridium perfringens Glycan arrays revealed its preference towards α(2,3)-linked sialosides, which was confirmed and quantified by calorimetric studies. The CBM40 binds to α(2,3)-sialyl-lactose with a Kd of ∼30 μM, the highest affinity value for this class of proteins. Inspired by lectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 51 publications
3
45
0
Order By: Relevance
“…The α2,6-sialic acid-specific lectins SNA-I, TJA-I, and PSL-I showed an average 29% decrease in binding relative to the vehicle-treated control. Our engineered recombinant lectin diCBM40, which binds both α2,3and α2,6-linked sialic acids with similar affinity (22), showed a 35% loss in binding, further supporting a decrease in α2,6-sialylation. XBP1s activation also decreased bisecting N-glycans, as indicated by decreasing PHA-E signal ( Fig.…”
Section: Experimental Platform and Workflow To Scrutinize Effects Of supporting
confidence: 56%
“…The α2,6-sialic acid-specific lectins SNA-I, TJA-I, and PSL-I showed an average 29% decrease in binding relative to the vehicle-treated control. Our engineered recombinant lectin diCBM40, which binds both α2,3and α2,6-linked sialic acids with similar affinity (22), showed a 35% loss in binding, further supporting a decrease in α2,6-sialylation. XBP1s activation also decreased bisecting N-glycans, as indicated by decreasing PHA-E signal ( Fig.…”
Section: Experimental Platform and Workflow To Scrutinize Effects Of supporting
confidence: 56%
“… 18 We previously demonstrated that RSL can be engineered, resulting in neoRSL with controlled number of binding sites. 18 , 19 As for sialic acid, a CBM from the NanI sialidase of Clostridium perfringens ATCC13124 (CBM40_NanI) was selected as the protein candidate to be fused to RSL due to the relatively strong affinity for sialylated oligosaccharides ( K D = 32 μM for 3′-siallyllactose), 20 the ease of expression, and the accessibility of both C-ter and N-ter extremities for engineering ( Fig. 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…Creating such multivalent receptors through artificially constructed tandem repeats is a route of interest. It generally strongly enhances the receptor affinity for its ligand [54,55]. It has also been demonstrated that expression as tandem-repeat sequences improves the production of recombinant algal lectins in bacterial systems [56].…”
Section: Conclusion and Discussionmentioning
confidence: 99%